Bounded Epistemic Rationality and Norms of Inquiry - Nastja Tomat (Ars & Humanitas)
Epistemology has recently taken a zetetic turn: a shift in emphasis from the study of norms of belief to norms of inquiry. In this paper, I argue that a non-ideal approach to zetetic normativity can provide norms of inquiry for bounded, psychologically realistic agents. I introduce the concepts of non-ideal epistemology and bounded epistemic rationality and provide a brief overview of inquiry epistemology. I continue with proposing some features that should be included in the norms of inquiry for bounded agents. I argue that such norms should recognize our cognitive, environmental, and practical limitations. They should direct bounded agents to inquire about relevant problems, and they should be satisficing in nature, meaning that they allow for good enough reaching of epistemic goals. I argue that rational inquiry is not determined by a priori normative criteria, but is defined as the fit of the strategy with the environment. Inquiry epistemology for bounded agents should provide concrete, fine-grained zetetic norms that are achievable for ordinary inquirers and can serve as epistemic guidance. The study of norms of inquiry for bounded agents explores both normative and descriptive parts of inquiry, is ameliorative, partly empirical, and requires collaboration between philosophy and empirical disciplines such as psychology and cognitive science.